CORROSION BEHAVIOR OF SUPER AUSTENITIC STAINLESS STEEL, DUPLEX 2205 AND 316L IN SULFAMIC ACID ENVIRONMENT - Roszardi, Bashari R; Riastuti, Rini; Budiarto, Wahyu; Darsono, Nono; Syahid, Adi Noer (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2022)
Currently, sulfuric acid as a primary chemical industrial material is ubiquitous. One of its uses is a sweetener. Due to its corrosive nature, it is necessary to use a suitable container to avoid contamination of the solution. Corrosion behavior of super austenitic stainless steel, duplex 2205, and 316L uncovered to sulfamic acid in diverse attention at ambient temperature had been investigated. Concentration Weight loss method, Potentiodynamic Polarization, and Electrochemical Impedance Spectroscopy (EIS) examined the corrosion rate. The result showed that the corrosion rate of material increased with the increasing concentration of sulfamic acid. Super austenitic stainless steel has higher corrosion resistance than duplex 2205 and 316L.Â Â